A sampling-based speaker clustering using utterance-oriented Dirichlet process mixture model and its evaluation on large-scale data. (28th October 2015) - Tawara, Naohiro; Ogawa, Tetsuji; Watanabe, Shinji; Nakamura, Atsushi; Kobayashi, Tetsunori
Abstract : An infinite mixture model is applied to model-based speaker clustering with sampling-based optimization to make it possible to estimate the number of speakers. For this purpose, a framework of non-parametric Bayesian modeling is implemented with the Markov chain Monte Carlo and incorporated in the utterance-oriented speaker model. The proposed model is called the utterance-oriented Dirichlet process mixture model (UO-DPMM). The present paper demonstrates that UO-DPMM is successfully applied on large-scale data and outperforms the conventional hierarchical agglomerative clustering, especially for large amounts of utterances.